Hubungan antara daya tarik interpersonal dan keintiman generasi z di Universitas Negeri Malang - Alamanda Catartika; Fattah Hanurawan; Aji Bagus Priyambodo (Universitas Negeri Malang, 2021)
Abstract: This study aims to determine (1) the level of interpersonal attraction of Generation Z at State University of Malang, (2) the level of intimacy of Generation Z at State University of Malang, and (3) The correlation between interpersonal attraction and intimacy of Generation Z at State University of Malang. This research used quantitative method. The population of this research is 31090 people, and the sample is 240 people that used incidental sampling. The instrument in this study is the scale of interpersonal attraction made by the researchers themselves based on the McCroskey & McCain (1974) theory and intimacy scales made by the researchers themselves based on Orlofsky & Roades (Scharf & Ofra, 2001) theory. There are two data analysis techniques used, namely descriptive analysis and product moment correlation. The results of the descriptive analysis found that: (1) the level of interpersonal attraction on generation Z was in the high category, (2) the level of intimacy on generation Z was in the high category, and (3) there was a positive relationship between interpersonal attraction and intimacy on generation Z at State University of Malang. This research showed that correlation between variables has rxy = 0,185 and had p=0,004 < 0,05, so that Ha was accepted, and it showed that there was positive correlation between interpersonal attraction (X) and intimacy (Y) but it has weak correlation. Suggestions that can be given are (1) we expected for generation Z at State University of Malang have more attention and consider about attractiveness to other people, (2) for BEM Faculty of Psychology at State University of Malang with direction from the lectures, can give an information about attractiveness and intimacy of Generation Z, (3) further researchers are advised to have more attention to the variables and use bigger samples. Keywords: interpersonal attraction; intimacy Abstrak: Penelitian ini bertujuan untuk mengetahui (1) tingkat daya tarik interpersonal generasi Z di Universitas Negeri Malang, (2) tingkat keintiman generasi Z di Universitas Negeri Malang, dan (3) hubungan daya tarik interpersonal dan keintiman generasi Z di Universitas Negeri Malang. Penelitian ini menggunakan metode penelitian kuantitatif dengan pendekatan deskriptif korelasional. Penelitian ini melibatkan 31090 populasi dengan 240 sampel menggunakan insidental sampling. Instrumen penelitian ini adalah skala daya tarik interpersonal yang dibuat oleh peneliti sendiri berdasarkan teori McCroskey & McCain (1974) dan skala keintiman yang dibuat oleh peneliti sendiri berdasarkan teori Orlofsky & Roades (Scharf & Ofra, 2001). Hasil penelitian menunjukkan (1) tingkat daya tarik interpersonal generasi Z dalam kategori tinggi, (2) tingkat keintiman generasi Z dalam kategori tinggi, (3) ada korelasi positif antara daya tarik interpersonal dan keintiman generasi Z di Universitas Negeri Malang. Hasil perhitungan korelasi pada penelitian ini menggunakan product moment, menunjukkan bahwa daya tarik interpersonal dan keintiman memiliki rxy sebesar 0,185 dengan nilai signifikansi 0,004 < 0,05 sehingga hipotesis diterima. Berdasarkan Hal ini terdapat hubungan antara daya tarik interpersonal (X) dan keintiman (Y) yang memiliki korelasi positif di kategori lemah. Saran penelitian adalah (1) bagi generasi Z dapat lebih memperhatikan dan melakukan pertimbangan untuk memiliki ketertarikan pada orang lain jika menimbulkan rasa suka. (2) bagi BEM Fakultas Pendidikan Psikologi Universitas Negeri Malang turut serta dalam memberikan penyuluhan daya tarik interpersonal dan keintiman dan (3) bagi peneliti selanjutnya dapat untuk mengkaji lebih dalam penelitian yang serupa serta dengan sampel yang lebih besar. Kata kunci: daya tarik interpersonal; keintiman